PENGARUH KUALITAS PELAYANAN, HARGA, DAN KUALITAS WEBSITE TERHADAP KEPUASAN PELANGGAN - Agus Wahyono (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2018)
This report aims to review the influence of the quality of service , prices and the quality of customer satisfaction website .Methods used in research is quantitative methods and results of the study is based on the answers to the questionnaire given to use likert respondents scale .The population of the research is students usni in 1889 and samples to this study were 100 respondents .The method of analysis on this research using analysis desktiptif , the instrument (validity and normality), the assumption (normality classic, heteroskedastisitas , multikolonieritas and autokorelasi ) , regression analysis linear multiple , the t , the f and koefesien determinan R². From the results of the test t , have the results showed that variable the quality of the services they provide ( x1 ), of prices ( x2 ) and the quality of the services they provide ( x3 ) has had the influence and significant impact on usni student satisfaction .Of the trial f, the results showed that third variable influential and significant impact on usni student satisfaction .